Juvenilização na educação de jovens e adultos (EJA): o caso da Escola Municipal Professora Inah de Medeiros Dantas, na cidade de Caicó - RN - Souza, Elianete Maria Medeiros de (2022)
This work aims to verify the motivations that lead to the process of youthfulness in the teaching modality of Youth and Adult Education (EJA), at the Municipal School Professora Inah de Medeiros Dantas. With this reflection, knowledge of the data is based on the qualitative approach, according to Ludke and André (2013). With regard to the methodological basis, we start from a bibliographical review of authors who deal with the subject, such as: Freire (2013), Carrano (2007), Sposati (2005), Lódi (2019). From this review, we understand the presence of youth in EJA, the challenges and possibilities in this teaching modality. In order to get to know the school and the research subjects, we started with data from Qedu (2021), in addition to a field research at the school where the study was carried out, with the purpose of observing the school structure, and we applied questionnaires as EJA students in search of obtaining results. The reflections make it clear that young people have increasingly entered EJA, in which this modality was initially characterized by the predominance of adults. As soon as this teaching modality is formative, humanizing to these young people who are inserted in the EJA. We hope that this work can be a source of reflection for education in the city of Caicó/RN, so that teachers understand the social context of each student inserted in EJA. In addition, this work allows other researchers to problematize, investigate and reflect on the performance of other studies on the aforementioned theme.